A Historical Perspective on the Identification of Cell Types in Pancreatic Islets of Langerhans by Staining and Histochemical Techniques. (August 2015) - Baskin, Denis G.
Before the middle of the previous century, cell types of the pancreatic islets of Langerhans were identified primarily on the basis of their color reactions with histological dyes. At that time, the chemical basis for the staining properties of islet cells in relation to the identity, chemistry and structure of their hormones was not fully understood. Nevertheless, the definitive islet cell types that secrete glucagon, insulin, and somatostatin (A, B, and D cells, respectively) could reliably be differentiated from each other with staining protocols that involved variations of one or more tinctorial techniques, such as the Mallory-Heidenhain azan trichrome, chromium hematoxylin and phloxine, aldehyde fuchsin, and silver impregnation methods, which were popularly used until supplanted by immunohistochemical techniques. Before antibody-based staining methods, the most bona fide histochemical techniques for the identification of islet B cells were based on the detection of sulfhydryl and disulfide groups of insulin. The application of the classical islet tinctorial staining methods for pathophysiological studies and physiological experiments was fundamental to our understanding of islet architecture and the physiological roles of A and B cells in glucose regulation and diabetes.